(untitled) (Revista Contexto & Educação, 2022)
The present study sought to analyze whether the strategies implemented in one of the pedagogical spaces of a professional and technological education institution in Northern Brazil can be considered participatory. The methodological path consisted of data collection made through a semi-structured interview script with the participants to formulate and implement strategies for conducting a mini-course on the Moodle platform, the studied pedagogical space. The data were organized, analyzed, and interpreted using semantic and content analysis techniques. The results showed that a) the respondents have different perceptions about the objectives of the course, b) presented different views about the stages of the project’s execution, c) there was a harmony of their perceptions about the benefits of the project, and d) the respondents were unanimous in considering that there were many setbacks for the practice of participatory management. The conclusion shows no full participation in the formulation and execution of the analyzed pedagogical space strategies.